Was the negative impact of EU accession on VAT revenue only short-term? - Markovič-Hribernik, Tanja (Naše gospodarstvo, 2006)
Slovenia joined the EU on May 1, 2004. Some of the effects of its accession were expected and predicted in advance. Nevertheless, in some segments, considerable deviations occurred. Revenues from VAT are one such example. We started investigating the reasons behind the unexpected loss of revenue from VAT in the beginning of 2005. We were analysing past movements of VAT payments and refunds and trying to predict the dynamism and scope of VAT revenue in 2005 and 2006. We compared the data about the actual realisation of VAT revenues in 2005 with our estimates. Thus, we could examine how accurate our estimates were, and try to find the answer to the question of whether a huge unexpected loss of VAT revenues in 2004 was only a short-term and one-off phenomenon or if smaller revenues can also be expected in future tax periods.
Keywords: European Union; Evropska unija; Slovenia; Slovenija; integracija; davki; tax; davek na dodano vrednost; državni proračun